The Aramaeans in ancient Syria - Niehr, Herbert. (Handbook of Oriental Studies. Section 1 The Near and Middle East, 2014)
The historical and cultural role of the Aramaeans in ancient Syria can hardly be overestimated. Thus The Aramaeans in Ancient Syria gives precise and up-to-date information on different aspects of Aramaean culture. To that end, history, society, economy and law, language and script, literature, religion, art and architecture of the Aramaean kingdoms of Syria from their beginnings in the 11 century B.C. until their end at approximately 720 B.C. are covered within the handbook. The wide survey of Aramaean culture in Syria is supplemented by overviews on the Aramaeans in Assyria, Babylonia, Phoenicia, Palestine, Egypt, North Arabia and on the Aramaean heritage in the Levant.